2013
DOI: 10.1111/and.12127
|View full text |Cite
|
Sign up to set email alerts
|

A computational bioinformatics analysis of gene expression identifies candidate agents for prostate cancer

Abstract: Prostate cancer is the second most frequently diagnosed cancer and the sixth leading cause of cancer death in males worldwide. Although great progress has been made, the molecular mechanisms of prostate cancer are far from being fully understood and treatment of this disease remains palliative. In this study, we sought to explore the molecular mechanism of prostate cancer and then identify biologically active small molecules capable of targeting prostate cancer using a computational bioinformatics analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Equivalently important, it is necessary to identify and validate new molecular drug targets in order to develop underlying therapeutic agents that may be successful in remedying prostate cancer. Surprisingly, most researches concentrate on an individual genetic result or the results are derived from an alone cohort research through microarray analysis which is not uniform with each other (Derosa et al, ; Mortensen et al, ; Satake et al, ; Wen, Geng, Li, Guo, & Zheng, ). Our study integrated four cohorts profile data sets from different groups, utilised bioinformatics methods to deeply analyse these data sets and identified 217 significantly changed DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalently important, it is necessary to identify and validate new molecular drug targets in order to develop underlying therapeutic agents that may be successful in remedying prostate cancer. Surprisingly, most researches concentrate on an individual genetic result or the results are derived from an alone cohort research through microarray analysis which is not uniform with each other (Derosa et al, ; Mortensen et al, ; Satake et al, ; Wen, Geng, Li, Guo, & Zheng, ). Our study integrated four cohorts profile data sets from different groups, utilised bioinformatics methods to deeply analyse these data sets and identified 217 significantly changed DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…It could be interesting to explore 8-azaguanine as an anti-Prostate Cancer drug. In a recent study Wen et al (2013) also indicated 8-azaguanine for potential therapeutic efficacy in prostate cancer. the activity, while the rest of the structure is just needed to maintain the shape.…”
Section: Drug Descriptionmentioning
confidence: 98%
“…High proliferative and antiapoptotic potential are related to the up-regulation of growth hormone receptor and calmodulins [ 31 ]. The top 20 genes which were found to be up-regulated in SCC early passage cells in comparison to SCC horn tissue were investigated to have roles in other cancers as well as SCC in human and domestic animals ( Table-7 ) [ 32 - 61 ] and vice versa ( Table-8 ) [ 62 - 95 ].…”
Section: Resultsmentioning
confidence: 99%